Tracking filter engineering : the Gauss-Newton and polynomial filters - Morrison, Norman (IET radar, sonar, navigation and avionics series, 2013)
Identifying an alternative approach to filter engineering and the traditional Kalman filters, this new book highlights the important advantages of the Gauss-Newton filters.